Lycopene inhibits ER stress and apoptosis while modulating PI3K/AKT and enhancing antioxidant and anti-apoptotic proteins - Lijun Zheng; Hui Zhang; Yuchao Sun (PLoS ONE, 2025)
Acute kidney injury (AKI) is a critical clinical syndrome with limited therapeutic options. This study investigated the renoprotective effects of lycopene, a potent antioxidant, in both in vivo and in vitro AKI models. In a murine cecal ligation and puncture (CLP)-induced sepsis-AKI model, pretreatment with lycopene (10, 20, 40 mg/kg) dose-dependently ameliorated renal histopathological damage (HE staining) and restored serum biomarkers (AST, ALT, BUN, CREA). Mechanistically, lycopene suppressed oxidative stress and apoptosis by downregulating the PI3K/Akt axis: it significantly reversed the CLP-induced upregulating of p-PI3K and p-Akt, and the pro-apoptotic proteins (Bax, Cleaved Caspase-3), while increasing Nrf 2 and SOD1. Consistent results were observed in LPS- and H₂O₂-induced cellular AKI models, where lycopene attenuated cell death and restored redox homeostasis in a dose-dependent manner. Immunofluorescence assays further validated these trends. Crucially, PI3K siRNA or cDNA transfection experiments confirmed that lycopene’s antioxidant and anti-apoptotic effects were PI3K-dependent. Our findings highlight lycopene as a promising therapeutic agent for AKI, acting via PI3K/Akt-mediated activation of Nrf 2 to counteract oxidative damage and apoptosis. This study provides novel insights into the molecular mechanisms underlying lycopene’s renoprotection and supports its potential clinical translation for sepsis or oxidative stress-associated AKI.